KACANG KEDELAI HITAM DAN KACANG HIJAU SEBAGAI MEDIA ALTERNATIF PERTUMBUHAN Pseudomonas aeruginosa ATCC 15442 TERHADAP MEDIA PAB - Vivi Zumrotin; Dian Rachma Wijayanti; Intan Kurniawati Pramitaningrum (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Black soybeans (Glycine soja L. Merr) and green beans (Vigna radiata) are sources of protein and carbohydrates. The background of this study is the lack of development of natural semi-synthetic microbiological media from beans. The purpose of this study was to determine the growth and optimum concentration of Pseudomonas aeruginosa ATCC 15442 bacteria on alternative black soybean media, alternative green bean media with PAB control media. This type of research is a continuous experiment, posttest only control group design. The samples in this study were alternative black soybean and green bean media with concentrations of 5.5%, 10.5%, and 15.5%. The research data were analyzed descriptively and statistically. The results of the study showed that P. aeruginosa ATCC 15442 bacteria grew in all treatments. The average number of P. aeruginosa bacteria on PAB media was 64.67 x  CFU/mL. The average number of P. aeruginosa bacteria in the alternative black soybean media with a concentration of 15.5% was 77 x CFU/mL. The average number of P. aeruginosa bacteria in the alternative mung bean media with a concentration of 15.5% was 91.33 x  CFU/mL. The results of the statistical analysis of the One Way ANOVA Test followed by the Post Hoc Test obtained a significance value of 1.000 and 0.999. The alternative black soybean media and the alternative mung bean media with a concentration of 15.5% had a higher average number of colonies than the PAB control media.